Beeld van de Vrouw. - Dewilde, Michel; Vandewalle, Luc; vzw De Gulden Sporen (Kortrijk : BBL (Bank Brussel Lambert), 1992)
Axell, Evelyne ; Baes, Firmin ; Boudry, Aloïs ; Buisseret, Louis ; Canestraro, Livia ; Ciamberiani, Albert ; Claus, Emile ; De Bruycker, Jules ; De Hem, Louise ; De Jonghe, Gustaaf ; Delville, Jean ; Douard, Cécile ; Ensor, James ; Frederic, Léon ; Joostens, Paul ; Lafontaine, Marie-Jo ; Leveque, Auguste ; Minne, George ; Montigny, Jenny ; Permeke, Constant ; Rops, Félicien ; Sauer, Walter ; Spilliaert, Léon ; Tapta ; Tasseel, Nadine ; Van Rysselberghe, Theo ; Verdegem, Jos ; Verduyn, Jacques ; Vertessen, Liliane ; Wappers, Gustaaf ; Wiertz, Antoine ; Wittevrongel, Roger ; Wouters, Rik
biog. p. 47-51
Nederlands
Beeld van de Vrouw, BBL (Bank Brussel Lambert) - Zetel Kortrijk, 17 december 1992 - 6 februari 1993
boek